Zwitterionic 3D‐Printed Non‐Immunogenic Stealth Microrobots. Issue 42 (30th August 2020) - Cabanach, Pol; Pena‐Francesch, Abdon; Sheehan, Devin; Bozuyuk, Ugur; Yasa, Oncay; Borros, Salvador; Sitti, Metin
Abstract: Microrobots offer transformative solutions for non‐invasive medical interventions due to their small size and untethered operation inside the human body. However, they must face the immune system as a natural protection mechanism against foreign threats. Here, non‐immunogenic stealth zwitterionic microrobots that avoid recognition from immune cells are introduced. Fully zwitterionic photoresists are developed for two‐photon polymerization 3D microprinting of hydrogel microrobots with ample functionalization: tunable mechanical properties, anti‐biofouling and non‐immunogenic properties, functionalization for magnetic actuation, encapsulation of biomolecules, and surface functionalization for drug delivery. Stealth microrobots avoid detection by macrophage cells of the innate immune system after exhaustive inspection (> 90 hours), which has not been achieved in any microrobotic platform to date. These versatile zwitterionic materials eliminate a major roadblock in the development of biocompatible microrobots, and will serve as a toolbox of non‐immunogenic materials for medical microrobot and other device technologies for bioengineering and biomedical applications. Abstract : Zwitterionic stealth microrobots avoid detection and capture by immune cells. Zwitterionic microrobots with anti‐biofouling, stealth, and non‐immunogenic properties are 3D‐printed via two‐photon‐polymerization, and are functionalized for magnetic actuation, encapsulation of biomolecules, and drug delivery. The microrobots remain undetected by macrophages and other immune cells for at least 90 hours, overcoming a major roadblock in medical microrobotics.